Bispectral index value for insertion of laryngeal mask airway while performing the jaw thrust maneuver under general anesthesia: A Cross-sectional Descriptive Study - Tamrongchote, Suwitcha; Keawkulsri, Nongnooch; Udomlap, Patnasorhn (Health Science Clinical Research, 2025)
Objective: To evaluate the actual Bispectral index value while performing the jaw thrust maneuver for laryngeal mask airway insertion under general anesthesia Methods: 110 ASA class I or II elective surgical patients with age between 18-65 years old who undergoing general anesthesia with laryngeal mask airway insertion were enrolled for study. Intraoperative Bispectral index values and hemodynamic variability were measured before induction, at the time jaw thrust maneuver success, just ater LMA insertion and then at 1, 3 and 5 minutes, including the post-anesthetic airway complications and awareness Results: Bispectral index value while performing the jaw thrust maneuver for laryngeal mask airway insertion under general anesthesia were 34.59±6.28. Other Bispectral index values in each period of time were 91.78±6.19, 36.36±8.74, 32.89±9.83, 31.49±9.73 and 41.98±12.27 at induction, just after appropriated LMA insertion and 1, 3 and 5 minutes respectively. Tread of hemodynamic profiles such as the mean of MAP and HR were decreasing, especially in elderly group at each time periods after induction while desaturation or airway complications were not found. The lowest mean MAP and mean HR values were at 1 minute and 3 minutes in order after successful insertion. The mean of Bispectral index values, MAP and HR were found in the same direction but without statistical significance (p>0.05) Conclusions: The Bispectral index value that corresponds to jaw thrust maneuver for testing the appropriate depth of anesthesia for LMA insertion is mostly lower than 40. No statistically significant relation ship was found between the effects of low Bispectral index values on the mean of blood pressure or heart rate.